Cyanide in cassava: unveiling health risks in the lens of unsustainable food systems in Sub-Saharan Africa – a systematic review - Gareth Osman; Wyson Maleta; Kingsley Masamba; Tinna Ng'ong'ola-Manani; Alexander A. Kalimbira (Frontiers in Sustainable Food Systems)
ObjectiveCassava (Manihot esculenta Crantz) remains a vital staple crop across Sub-Saharan Africa (SSA), sustaining millions of livelihoods. However, its consumption poses a significant public health concern due to the presence of cyanogenic glycosides. This systematic review synthesizes evidence on the health impacts of cyanide exposure from cassava consumption in SSA and examines how these risks are shaped by structural vulnerabilities in food systems.MethodsA comprehensive literature search was conducted across four databases: PubMed, Scopus, JSTOR, and AJOL. Retrieved publications were organized using Mendeley Desktop. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two independent reviewers carried out the search and screening processes, with any disagreements resolved through discussion with a third reviewer. The review included human epidemiological studies—observational, interventional, and clinical—that examined the health impacts of dietary cassava intake among populations in SSA. The keywords used in the search included cassava, cyanide, hydrogen cyanide, linamarin, lotaustralin, cyanogenic glycosides, konzo, health risk, acute poisoning, toxicity, tropical ataxic neuropathy, and neurological disorder. The initial search was conducted in January 2025 and updated on 24th June 2025.ResultsThe review identified 45 relevant studies, with the majority conducted in the Democratic Republic of Congo (n = 18), followed by Mozambique (n = 10), Tanzania (n = 7), and Nigeria (n = 6). Urinary thiocyanate levels often exceeded the World Health Organization's safety threshold of 350 μmol/L, reaching up to 1,730 μmol/L, particularly among individuals affected by konzo. These adverse health outcomes were often compounded by armed conflict, drought, poor infrastructure, and protein-deficient diets. Climate-related stressors, such as El Niño events and prolonged dry spells may further intensify reliance on cassava, resulting in the consumption of inadequately processed roots. Residual Hydrogen Cyanide (HCN) concentrations in cassava products varied widely depending on the processing method. Among these, the wetting method consistently achieved the greatest reductions, lowering HCN levels to as little as 4 ppm.ConclusionCyanide exposure from cassava remains a significant public health concern in SSA, particularly in areas with fragile food systems and limited access to safe processing methods. Strengthening food system resilience, expanding access to safer cassava cultivars (e.g., biofortified cassava varieties), and promoting effective processing methods such as wetting, are essential strategies for reducing cassava-related health risks.